A comparative analysis of saponin-enriched fraction from Silene vulgaris (Moench) Garcke, Sapindus mukorossi (Gaertn) and Chlorophytum borivilianum (Santapau and Fernandes): an in vitro hemolytic and cytotoxicity evaluation. Issue 1 (1st February 2022) - Singh, Rahul; Sharma, Rinku; Mal, Gorakh; Varshney, Rajat
Abstract: To explore the newer saponin resources, in vitro toxicity of saponin-enriched fraction (SEF) extracted from Silene vulgaris (SV) was evaluated for first time and compared with in vitro toxicity of SEF extracted from Sapindus mukorossi (SM) and Chlorophytum borivilianum (CV). All extracted SEF from diverse resources were characterized by immersing TLC plates in 0.5% RBC suspension method, by ethanol: sulfuric acid method and by estimating hRst values. Each extracted SEF clearly portrayed specific pattern with varied hRst range. White spots against a pinkish-red background and greenish-black spots in case of immersion method and spraying method respectively were observed. After initial characterization, in vitro 0.5% sheep RBC lytic activities and VERO cell cytotoxic activities (via SRB assay) of each extracted SEF were also evaluated. Furthermore, SEF of SV showed very less hemolytic activity compared to SM and CB. The HD50 values for SV, SM, and CB were 736.7 ± 2.824, 18.0 ± 1.894, and 170.70 ± 2.783 µg/mL, respectively. SEF of SV (IC50 ≥ 200 µg/mL) was less toxic for VERO cell line than SEF of SM (IC50 = 150.8 µg/mL) and CB (IC50 = 137.1 µg/mL). Hence, the SEF of SV was found to be less toxic and can be used as a new and safer source of saponins. Graphical Abstract: UF0001